2018
DOI: 10.1051/matecconf/201817003015
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of medical architecture

Abstract: This article deals with the history of medical architecture development in Russia and abroad. Numerous examples of buildings of healthcare facilities, from ancient times to the present day, are given. Buildings of hospitals and clinics were erected in the architectural traditions then prevailing. Features of healthcare facilities, which determine their architectural concept, are: type and purpose of the healthcare facility, scope and structure of medical services, location in the urban environment, architectur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…It was established under the monastic hospital auspices in the 9th century in Italy [38]. It is confirmed that the Schola Medica Salernitana remained the ground-breaking center for training scientists and medical professionals and for the provision of licensed practice in Europe until the 13th century [40].…”
Section: Hospital Architecture Evolution Overviewmentioning
confidence: 95%
See 1 more Smart Citation
“…It was established under the monastic hospital auspices in the 9th century in Italy [38]. It is confirmed that the Schola Medica Salernitana remained the ground-breaking center for training scientists and medical professionals and for the provision of licensed practice in Europe until the 13th century [40].…”
Section: Hospital Architecture Evolution Overviewmentioning
confidence: 95%
“…Moreover, the appropriate building relevance in healing processes is well recognized by both architectural and medical practitioners. The social functions dominated hospitals in the early Middle Ages, as opposed to the medical, after the old states fell; the hospitals are associated with low medical-knowledge levels [40]. However, numerous hospitals were launched between the 6th and 8th centuries in Western Europe.…”
Section: Hospital Architecture Evolution Overviewmentioning
confidence: 99%
“…In the early Middle Age, hospitals were dominated by social functions as against medical after the fall of the ancient states, owed to the low level of medical knowledge [ 11 ]. Nevertheless, in Western Europe, between the 6th and 8th centuries, numerous hospitals were launched.…”
Section: Review Of Evolution Of Medical Architecture and Infectious Dmentioning
confidence: 99%
“…The earliest chronicles of health-care in Egypt and Greece are knotted to spiritual tenets with priests and sanctuaries playing key parts in an attempt at disease identification, analysis and care. Many of the early hospital designs resembled schools structured around a courtyard often located at the edge of villages or cities and monastic orders were the caretakers of the sick [ 11 , 13 ]. A good example of such a building is “Schola Medica Salernitana founded in the 9 th century under the auspices of the monastic hospital in Italy” [ 10 ].…”
Section: Review Of Evolution Of Medical Architecture and Infectious Dmentioning
confidence: 99%
See 1 more Smart Citation